The Effektivenes of Imagery Intervention on Reducing Competitive Anxiety Levels In Indonesian Army Shooting Athletes - Muchamad Ginanjar Pratama Sudrajat; Eneng Nurlaili Wangi; Irfan Fahmi (Eduvest - Journal of Universal Studies, 2025)
Competition tests athletes by demanding peak performance under pressure from both their environment and themselves, aiming for victory. One common challenge they face is Competitive Anxiety, a response to perceived threats in competitive situations, leading to worry or stress (Martens, 1977). The ASEAN Armies Rifle Meet (AARM) is the highest-level competition for Indonesian Army marksmen. This study examines the effectiveness of the Mental Imagery Technique in reducing competitive anxiety among female AARM athletes. This cognitive-based intervention uses mental visualization of past experiences to enhance performance. Using an experimental one-group pretest-posttest design, the study involved five participants (n=5), with data analyzed through a Paired T-Test. Results showed a significant reduction in Competitive Anxiety scores post-intervention (Asymp. sig 0.000 < 0.05). N-Gain scores indicated moderate effectiveness for two respondents (-69% and -60%) and high effectiveness for three respondents (>76%). These findings confirm that the Mental Imagery Technique effectively reduces competitive anxiety in female pistol shooters at AARM. This study suggests that mental imagery is a valuable psychological strategy for managing anxiety in high-pressure sports, particularly for female athletes in precision disciplines like shooting.